Education Differences in Women's Body Weight Trajectories: The Role of Motherhood - Hannes Kröger; Liliya Leopold (PLOS ONE, 2020)
Studies have found that education differences in women's body weight increase until middle adulthood. The explanatory mechanisms behind this increase are not well-understood. This study examined the role of education differences in the prevalence of motherhood as a risk factor for weight gain and in vulnerability to its effects on weight gain. We used longitudinal data from the German Socio-economic Panel Study. Our sample included 2,668 women aged between 17 and 45 and observed at least twice between 2002 and 2016 (n = 13,899 panel observations). We used OLS regression models to estimate initial education differences in body weight and fixed-effects panel regression models to estimate education differences in body-weight trajectories. Motherhood was associated with increasing body weight, and the effects of motherhood on weight gain varied by education. Motherhood partially accounted for the increase of education differences during reproductive age. Until the age of 30, differences in the prevalence of motherhood accounted for about 20% of the bodyweight gap between lower and higher educated women. From age 35 until 45, differential vulnerability to the effects of motherhood on body weight explained about 15% of the education gap in body weight.
Keywords: 330; Body weight; Weight gain; Children; Pregnancy; Economics of training and education; Overweight; Medical risk factors; Obesity